The Influence Of Cross-Functional Collaboration, Top Management Support And Employee Digital Competence On Digital Innovation Capability In Multinational Service Companies - Yanuar Latief; Haris Karyadi; Kushariyadi Kushariyadi; Iwan Henri Kusnadi; Baren Sipayung; Hakim Hakim (Institute of Advanced Knowledge and Science, 2026)
This study aims to explore the influence of Cross-Functional Collaboration, Top Management Support and Employee Digital Competence on Digital Innovation Capability in a global service business. This study integrates quantitative research methodologies and survey methods by giving questionnaires to 210 workers and managers of a worldwide service firm by employing purposive sample approach. The prerequisites of respondents were that they had been working for at least two years, were active in the use of digital technology in their professional activities and had experienced the use of digital technology in the context of innovation or digital transformation efforts. The data analysis method was multiple linear regression Prior to the study, the data were tested for validity, reliability, normalcy, heteroscedasticity, and multicollinearity, as well as classical assumption tests. The results indicated that Cross-Functional Collaboration, Top Management Support, and Employee Digital Competence had a partial and simultaneous positive and significant effect on Digital Innovation Capability. The findings of the research reveal that an organization’s digital innovation skills may be strengthened by strengthening cross-functional collaboration, active support from top management and developing digital competencies of workers.